PS-BBICS: Pulse stretching bulk built-in current sensor for on-chip measurement of single event transients. (November 2022) - Andjelkovic, Marko; Marjanovic, Milos; Chen, Junchao; Ilic, Stefan; Ristic, Goran; Krstic, Milos
Abstract: The bulk built-in current sensor (BBICS) is a cost-effective solution for detection of energetic particle strikes in integrated circuits. With an appropriate number of BBICSs distributed across the chip, the soft error locations can be identified, and the dynamic fault-tolerant mechanisms can be activated locally to correct the soft errors in the affected logic. In this work, we introduce a pulse stretching BBICS (PS-BBICS) constructed by connecting a standard BBICS and a custom-designed pulse stretching cell. The aim of PS-BBICS is to enable the on-chip measurement of the single event transient (SET) pulse width, allowing to detect the linear energy transfer (LET) of incident particles, and thus assess more accurately the radiation conditions. Based on Spectre simulations, we have shown that for the LET from 1 to 100 MeV cm 2 mg −1, the SET pulse width detected by PS-BBICS varies by 620–800 ps. The threshold LET of PS-BBICS increases linearly with the number of monitored inverters, and it is around 1.7 MeV cm 2 mg −1 for ten monitored inverters. On the other hand, the SET pulse width is independent of the number of monitored inverters for LET > 4 MeV cm 2 mg −1 . It was shown that supply voltage, temperature and process variations have strong impact on the response of PS-BBICS. Highlights: A pulse stretching bulk built-in current sensor (PS-BBICS) for on-chip SET pulse width measurement is proposed. PS-BBICS extends the standard three-transistor BBICS by adding a pulse stretcher composed of two custom-sized inverters. Simulations have shown that for LET from 1 to 100 MeV cm 2 mg −1, the SET pulse width varies by 620–800 ps. For up to 10 monitored inverters, the SET pulse width is almost independent of the number of inverters. The SET pulse width is affected by supply voltage, temperature and process corners.